Metabolic syndrome is not only a risk factor for cardiovascular diseases in systemic lupus erythematosus but is also associated with cumulative organ damage: a cross-sectional analysis of 311 patients. (February 2016) - Demir, S; Artim-Esen, B; Şahinkaya, Y; Pehlivan, Ö; Alpay-Kanıtez, N; Omma, A; Erer, B; Kamalı, S; Gül, A; Aral, O; Öcal, L; İnanç, M
Background/Purpose: Patients with systemic lupus erythematosus (SLE) have increased rates of cardiovascular disease (CVD) that are one of the major causes of mortality. The aim of this study was to determine the frequencies of metabolic syndrome (MetS) and CVD in SLE patients and investigate the link between these and clinical features of SLE. Methods: A total of 311 SLE patients were consecutively assessed for cumulative organ damage (SDI/SLICC scores), history of CVD and MetS as defined by the National Cholesterol Educational Program Adult Treatment Panel III (NCEP ATP III). Clinical data of SLE patients were collected from the records. Results: The mean age of the patients was 40.2 ± 13.4 years and 89% were female. The frequencies of CVD and MetS were 15.2% and 19%, respectively. In this SLE cohort increased age, cumulative damage, disease duration and CVD were associated with MetS. CVD was associated with disease duration, cumulative damage, pericarditis, hematologic involvement, lymphopenia, thrombocytopenia, neurological involvement and antiphospholipid antibody (aPL) positivity. Hydroxychloroquine (HCQ) use was found as a protective factor for CVD. Conclusion: In SLE patients, MetS was associated with CVD and both increased with disease duration. Patients who developed MetS and/or CVD had increased cumulative organ damage. Certain clinical features of SLE and the presence of aPL were also associated with CVD. There was a significant protective effect of HCQ from CVD. The prevention of MetS and long-term use of HCQ may be beneficial in improving the prognosis of SLE.